O docente na corda bamba: o impacto da precarização laboral na subjetividade dos professores da rede pública de ensino do Estado do Ceará - Barros, Daniel Ítalo Alencar (2014)
This work intends to analyze the new ways of organization in the labour world and its consequences into the worker´s subjectivy, showing how the process of precariouness and flexibility are realized by them. We know that the process of precariouness is not homogeneous, reaching by many different ways the varied departments of workers. The studies about the labour reality of professors in public system os the state of Ceará – Brazil suplies from Work Sociology and Work´s Social Psychology. The methodology that has been used is based on the concept of social-hermeneutic by Alonso (1998). This choice provides a deep understanding about the teachers´ perception of precariouness and flexibility in their jobs. Theirs speaches about the meaning of work point to a perception of unhapiness with the activities and payment, further the conditions and time spent at work.